Using Selection on Observed Variables to Assess Bias from Unobservables when Evaluating Swan-Ganz Catheterization - Altonji, Joseph G; Elder, Todd E; Taber, Christopher R (American Economic Review, 2008)
Using Selection on Observed Variables to Assess Bias from Unobservables When Evaluating Swan-Ganz Catheterization by Joseph G. Altonji, Todd E. Elder and Christopher R. Taber. Published in volume 98, issue 2, pages 345-50 of American Economic Review, May 2008